(untitled) (Biological Sciences - PJSIR, 2010)
Abstract. Mesocarp and kernel oil of palm trees cultivated in two areas of Pakistan, Sindh (Thatta) and Balochistan were analysed for lipid contents, quality parameters and fatty acid profile. Oil content of mesocarp and the kernel of palm trees of Thatta, were found to be 68.23% and 26.4%, respectively, and those of Balochistan 62.7% and 27.79%, respectively. Fatty acid composition revealed the presence of palmitic (42.8%, 37.63%), oleic (34.3%, 43.54%) and linoleic acids (15.38%, 11.12%) as dominant fatty acids in the two mesocarp oils, while lauric acid (45.15%, 44.92%) was found as the most significant fatty acid in palm kernel oil of the two regions, respectively. Physical and chemical parameters such as density, refractive index, melting point, colour, free fatty acids, peroxide value, iodine value, saponification value and unsaponifiable matter of these four oils are also reported. Keywords: